Rhizospheric activity of phytoremediation species in soil contaminated with picloram1 - Souza,Wendel Magno de (2017)
ABSTRACT Some plant species have the ability to stimulate the microbiota activity in the rhizosphere and thereby increase the herbicide degradation in the soil. This study aimed at evaluating the microbial activity of soils contaminated with picloram and pre-cultivated with phytoremediation species. The experimental design was completely randomized, with three replicates. The treatments were organized in a 5 x 2 factorial scheme, with the first factor being the types of cultivation (autoclaved and non-autoclaved soil without cultivation and soil from the rhizosphere of Urochloa brizantha, Panicum maximum and Zea mays) and the second factor referring to the absence or presence (240 g ha-1) of picloram. The evolved C-CO2, microbial biomass carbon and metabolic quotient were estimated. The herbicide altered the evolved C-CO2, however, it did not affect the microbial biomass carbon and the metabolic quotient in the rhizospheric soils of the species. The cultivation of Zea mays increased the rhizosphere activity. The three plant species affect the soil microbial activity, however, the cultivation of Panicum maximum and Urochloa brizantha cause a lower disturbance on the microbial population, if compared to Zea mays. The picloran application does not affect the biological quality of the soils studied.